Investing in Well-being: An Analytical Framework - Veronica Jacobsen; Nicholas Mays; Ron Crawford; Barbara Annesley; Paul Christoffel; Grant Johnston; Sid Durbin (New Zealand Government, The Treasury, 2002)
The NZ Treasury is currently engaged in a project to identify cost-effective interventions to improve outcomes for children and young adults in order to maximise the value of government expenditures across the social sector. The central aim of this paper is to provide an empirically-robust framework to compare intervention across a range of social sectors. There are two key components to the framework. The first is a life-course view of child development that emphasises that experiences and influences in childhood can affect well-being throughout life. The second component involves viewing social expenditures as investments addressed at achieving particular outcomes, typically directed at enhancing well-being. The paper presents evidence from a review of the literature on how the process and experiences of childhood have a later impact on wellbeing; how child development and outcomes are influenced by individual, family and communal factors and how risk and resilience can be used to indicate that an individual is at increased or decreased risk of negative outcomes. Case studies of youth suicide, teenage pregnancy, educational underachievement and youth inactivity provide evidence about what interventions work using key empirical findings from the literature.
Keywords: J13; I31; H50; 330; Well-being; social investment; life-course; child development; child and adult outcomes; portfolio; intervention